The Emergence of Invasive Streptococcus pneumoniae Serotype 24F in Lebanon: Complete Genome Sequencing Reveals High Virulence and Antimicrobial Resistance Characteristics - Reslan, Lina; Finianos, Marc; Bitar, Ibrahim; Moumneh, Mohamad Bahij; Araj, George F.; Zaghlout, Alissar; Boutros, Celina; Jisr, Tamima; Nabulsi, Malak; Kara yaccoub, Gilbert; Hamze, Monzer; Osman, Marwan; et al. (Frontiers in Microbiology, 2021)
Background Invasive pneumococcal disease (IPD) remains a global health problem. IPD incidence has significantly decreased by the use of pneumococcal conjugate vaccines (PCV). Nevertheless, non-PCV serotypes remain a matter of concern. Eight Streptococcus pneumoniae serotype 24F isolates, belonging to a non-PCV serotype, were detected through the Lebanese Inter-Hospital Pneumococcal Surveillance Program. The aim of the study is to characterize phenotypic and genomic features of the 24F isolates in Lebanon. Methods WGS using long reads sequencing (PacBio) was performed to produce complete circular genomes and to determine clonality, antimicrobial resistance and virulence determinants. Results The sequencing results yielded eight closed circular genomes. Three multilocus sequence typing (MLST) types were identified (ST11618, ST14184, ST15253). Both MLST and WGS analyses revealed that these isolates from Lebanon were genetically homogenous belonging to clonal complex CC230 and clustered closely with isolates originating from Canada, United States of America, United Kingdom and Iceland. Their penicillin binding protein profiles correlated with both β-lactam susceptibility patterns and MLST types. Moreover, the isolates harbored the macrolide and tetracycline resistance genes and showed a similar virulence gene profile. To our knowledge, this study represents the first report of complete phenotypic and genomic characterization of the emerging Streptococcus pneumoniae, serotype 24F, in the Middle East and North Africa region.